К вопросу о взаимосвязи между названиями деревьев и птиц в балтийских языках - Радзявичюте, А. К. (Baltistica, 1987)
On the interconnection between the names of trees and birds in Baltic languages This paper is an attempt to prove the existence of bilateral connection between the names of birds and trees. The names of mountain-ash (Viburnum opulus L.) and snowball tree (Sorbus aucuparia L.) being often mixed, the semantic model “name of a bird” → “name of a tree” is suggested for both of them. The author of the paper suggests the existence of this model in the Lettish putenes (Viburnum opulus L.) : putns “bird” and gives a parallel etymological version of the Lithuanian pùtinas.